Globalization and bank efficiency nexus: Symbiosis or parasites? - Sufian, Fadzlan; Habibullah, Muzafar Shah (Science Direct, 2012)
The performance of the banking sector is a subject that has received academic and policymaker attention in recent years. The rapid pace of the financial sector liberalization further accentuates policymakers’ interest in the topic. To date, studies examining the performance of the Asian banking sectors are numerous. However, these studies have mainly concentrated on the impacts of banking sector restructuring and bank ownership issues, while empirical evidence on the impact of economic globalization is completely missing from the literature. In light of the knowledge gap, this study provides, for the first time, empirical evidence on the nexus between the level of globalization and the performance of the Indonesian banking sector during the period from 1999 to 2007.